Evaluasi Aktivitas Anti-Bakteri dan Anti-Oksidan Ekstrak n-Heksan, Etil Asetat dan Metanol Daun Pohpohan (Pilea melastomoides (Poir.) Weda.) - Violeta, Violeta; Kumala, Shirly (Jurnal Farmasi Indonesia, 2017)
ABSTRACT: Infection desease still a problem in developing country. The researcher search for the plant that have antibacterial agent to cure infection deseases. One the plant that the layman use to cured the infection deseases is Pohpohan (Pilea melastomoides (Poir.) Wedd) that containe flavonoids compunds. This study used n-hexane, ethyl acetate, and methanol extract as non-polar, semi-polar, and polar. This study aims to test the antibacterial activity and also antioxidants by multilevel extraction methods. The method used is extraction, with maceration of each stratum, each extract is done by phytochemical screening test with result of flavonoid compound, tannin, and essential oil. Thereafter, an antimicrobial test with a Staphylococcus aureus, and Escherichia coli microorganisms using a solid dilution method (Diameter of Inhibition Diameter) was performed with an extract concentration of 12.519: 2519: 5046, chloramphenicol used as positive controls. The result of antimicrobial assay had activity on n-hexane extract to form inhibit zone of 24.6 - 25.4 mm, ethyl acetate extract formed inhibit zone of 16.8 - 25.1 mm, While methanol extract formed inhibit zone of 15.1 - 23.3 mm, then Pohpohan leaf extract from each solvent was tested antioxidant by DPPH method, Result of antioxidant test (1IC50) of n-hexane extract (113.60 bpj), ethyl acetate (9444 bpj), and methanol (73.14 bpj). In conclusion, it shows that Pohpohan leaf extract has activity as antibacterial, andantioxidant. ABSTRACT: Infection desease still a problem in developing country. The researcher search for the plant that have antibacterial agent to cure infection deseases. One the plant that the layman use to cured the infection deseases is Pohpohan (Pilea melastomoides (Poir.) Wedd) that containe flavonoids compunds. This study used n-hexane, ethyl acetate, and methanol extract as non-polar, semi-polar, and polar. This study aims to test the antibacterial activity and also antioxidants by multilevel extraction methods. The method used is extraction, with maceration of each stratum, each extract is done by phytochemical screening test with result of flavonoid compound, tannin, and essential oil. Thereafter, an antimicrobial test with a Staphylococcus aureus, and Escherichia coli microorganisms using a solid dilution method (Diameter of Inhibition Diameter) was performed with an extract concentration of 12.519: 2519: 5046, chloramphenicol used as positive controls. The result of antimicrobial assay had activity on n-hexane extract to form inhibit zone of 24.6 - 25.4 mm, ethyl acetate extract formed inhibit zone of 16.8 - 25.1 mm, While methanol extract formed inhibit zone of 15.1 - 23.3 mm, then Pohpohan leaf extract from each solvent was tested antioxidant by DPPH method, Result of antioxidant test (1IC50) of n-hexane extract (113.60 bpj), ethyl acetate (9444 bpj), and methanol (73.14 bpj). In conclusion, it shows that Pohpohan leaf extract has activity as antibacterial, andantioxidant. ABSTRACT: Infection desease still a problem in developing country. The researcher search for the plant that have antibacterial agent to cure infection deseases. One the plant that the layman use to cured the infection deseases is Pohpohan (Pilea melastomoides (Poir.) Wedd) that containe flavonoids compunds. This study used n-hexane, ethyl acetate, and methanol extract as non-polar, semi-polar, and polar. This study aims to test the antibacterial activity and also antioxidants by multilevel extraction methods. The method used is extraction, with maceration of each stratum, each extract is done by phytochemical screening test with result of flavonoid compound, tannin, and essential oil. Thereafter, an antimicrobial test with a Staphylococcus aureus, and Escherichia coli microorganisms using a solid dilution method (Diameter of Inhibition Diameter) was performed with an extract concentration of 12.519: 2519: 5046, chloramphenicol used as positive controls. The result of antimicrobial assay had activity on n-hexane extract to form inhibit zone of 24.6 - 25.4 mm, ethyl acetate extract formed inhibit zone of 16.8 - 25.1 mm, While methanol extract formed inhibit zone of 15.1 - 23.3 mm, then Pohpohan leaf extract from each solvent was tested antioxidant by DPPH method, Result of antioxidant test (1IC50) of n-hexane extract (113.60 bpj), ethyl acetate (9444 bpj), and methanol (73.14 bpj). In conclusion, it shows that Pohpohan leaf extract has activity as antibacterial, andantioxidant.